Speed flow relationships and passenger car equivalent for truck in Philippine expressways - Mangubat, Frederick G.
This paper presents the results of a research on the capacity determination in the considered segments of North and South Luzon Expressways. This study focuses on the establishment of a speed flow curve. The peak of the curve could define the maximum rate of flow or capacity. The capacity being obtained in this study is being compared to the capacity obtained in other studies like the Highway Planning Manual which is prepared by the Ministry of Public Highways and the U.S. Highway Capacity Manual. This study also includes lane utilization analysis of the considered segments and a macroscopic approach in the estimation of passenger car equivalent for truck.